2007
DOI: 10.1016/j.jmmm.2006.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and magnetic properties of cobalt ferrite (CoFe2O4) nanoparticles prepared by wet chemical route

Abstract: Magnetic nanoparticles of cobalt ferrite have been synthesized by wet chemical method using stable ferric and cobalt salts with oleic acid as the surfactant. X-ray Diffraction (XRD) and Transmission Electron Microscope (TEM) confirmed the formation of single phase cobalt ferrite nanoparticles in the range 15-48nm depending on the annealing temperature and time. The size of the particles increases with annealing temperature and time while the coercivity goes through a maximum, peaking at around 28nm. A very lar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

36
340
2
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 856 publications
(380 citation statements)
references
References 12 publications
36
340
2
2
Order By: Relevance
“…Cobalt ferrite nanoparticles, which have formulation of CoFe 2 O 4, were synthesized by co-precipitation method (Maaz, Mumtaz, Hasanain, & Ceylan, 2007). The reactions regarding cobalt ferrite synthesis were given in the following equation.…”
Section: Preparation Of Cobalt Ferrite Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Cobalt ferrite nanoparticles, which have formulation of CoFe 2 O 4, were synthesized by co-precipitation method (Maaz, Mumtaz, Hasanain, & Ceylan, 2007). The reactions regarding cobalt ferrite synthesis were given in the following equation.…”
Section: Preparation Of Cobalt Ferrite Nanoparticlesmentioning
confidence: 99%
“…(Maaz, Mumtaz, Hasanain, & Ceylan, 2007). After obtaining the nanoparticles, washing process with ethanol and water was applied and precipitate was smashed and put in de-ionized water and it was vortexed.…”
Section: Preparation Of Cobalt Ferrite Nanoparticles By Using Oleic Acidmentioning
confidence: 99%
“…The decrease in saturation magnetization of all the samples compared to that of the bulk is ascribed to the surface effects in these nanoparticles. The existence of an inactive magnetic layer or a disordered layer on the surfaces of the nanoparticles and the heating rate of calcinations can be due to the decrease of saturation magnetization compared to the bulk value [38,39]. Figure 9 shows the M (H) loops of precursor and CoFe 2 O 4 nanoparticles that were measured at room temperature.…”
Section: Phase Composition and Morphology Of Precursors Andmentioning
confidence: 99%
“…With a further increase of calcination temperature over 1,100°C, the coercivity then exhibits a reduction tendency as the Ni 0.5 Co 0.5 Fe 2 O 4 grain size is larger than the single-domain size and the particles become multidomains. The domain-wall motions taking place in these multi-domain particles will result in the coercivity reduction [27]. It can be reasoned that the single-domain size of Ni 0.5 Co 0.5 Fe 2 O 4 in the nanocomposite Ni 0.5 Co 0.5 Fe 2 O 4 -BaTiO 3 fibers is around 65 nm, which is close to the value 70 nm for CoFe 2 O 4 particles reported by Rashada et al [28] and 100 nm for NiFe 2 O 4 particles reported by Yao et al [29].…”
Section: Magnetic Propertiesmentioning
confidence: 99%